Environment-friendly low-sulfur diesel oil anti-wear agent, preparation method and application thereof, and low-sulfur diesel oil anti-wear agent composition

Through the amidation reaction of rapeseed oil with diethylenetriamine and ricinoleic acid, combined with the modification and coating technology of the catalyst, an environmentally friendly low-sulfur diesel anti-wear agent was prepared, which solved the deflation point of the existing anti-wear agent. The problems of high and low temperature storage unstable and poor compatibility achieve excellent wear resistance and good diesel performance.

CN119462627AActive Publication Date: 2025-02-18SHANDONG YIPENG ENERGY DEV CO LTD

Patent Information

Application Number
CN202510075176.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-02-18
Estimated Expiration
2045-01-17

AI Technical Summary

Technical Problem

The existing low-sulfur diesel antiwear agents have problems such as high coagulation points, unstable low-temperature storage, poor compatibility and easy to cause blockage of fuel filters. The preparation process is complex and the cost is high, which affects the performance of diesel.

Method used

The dehydration reaction of rapeseed oil and diethylene triamine is used to produce imidazoline and amidate with ricinoleic acid to produce environmentally friendly low-sulfur diesel antiwear agent. This antiwear agent is improved by the modification and coating technology of catalysts. Its catalytic activity and dispersion are achieved.

Benefits of technology

This environmentally friendly low-sulfur diesel anti-wear agent has excellent wear resistance, is not very acidic, has little impact on the use performance of diesel, improves the anti-oxidation performance of diesel, is compatible with engine oil, and does not increase carbon deposits in the engine.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119462627A_ABST
    Figure CN119462627A_ABST
Patent Text Reader

Abstract

The invention provides an environment-friendly low-sulfur diesel oil anti-wear agent, a preparation method and application thereof and a low-sulfur diesel oil anti-wear agent composition, and belongs to the technical field of anti-wear agents. The environment-friendly low-sulfur diesel oil anti-wear agent has a structure shown in the specification. The environment-friendly low-sulfur diesel oil anti-wear agent prepared by the invention has the advantages of excellent anti-wear performance, low acidity, small influence on the use performance of diesel oil, such as corrosivity, combustion performance, total acid value, oxidation stability and the like, capability of improving the oxidation resistance of the diesel oil, compatibility with engine oil, no increase of carbon deposit in an engine, and wide application prospect. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of anti-wear agents, and in particular to an environmentally friendly low-sulfur diesel anti-wear agent, a preparation method and application thereof, and a low-sulfur diesel anti-wear agent composition. Background Art

[0002] Adding anti-wear agent to hydrogenated low-sulfur diesel is the simplest and most widely used method to improve diesel lubricity. It has the advantages of low cost, flexible production and less pollution, and is widely valued in the industry. Diesel anti-wear agent is usually a polar compound, mainly alcohol, ether, fatty acid, fatty acid ester and fatty amine and its derivatives. These compounds are a kind of oiliness agent, and the polar group is carboxyl or other nitrogen-containing and oxygen-containing groups. They are adsorbed on the metal surface, reducing the direct contact of the metal, playing the role of boundary lubrication and slowing down wear. The amount of anti-wear agent added varies according to the type of ingredients, concentration and type of diesel, and is generally 50-300ppm.

[0003] Alcohols and ethers have low polarity and weak lubrication effects, and require a high addition amount to achieve a certain effect. They are now rarely used. Fatty acid esters, amides, salts and other anti-wear agents are not widely used in China due to complex preparation processes, high costs, and poor product quality. In contrast, fatty acid type is the most commonly used diesel anti-wear agent in China due to its low price and good lubrication effect. Fatty acid anti-wear agents usually use a mixture of various saturated and unsaturated acids. When the saturated acid content is high or the chain length is long, its freezing point is high. The main shortcomings are as follows: ① It affects the cold filter point of diesel; ② At low temperatures, it will precipitate due to poor solubility in diesel, making the diesel turbid and affecting low-temperature storage stability; ③ There is a problem of poor compatibility between fatty acids and diesel or other additives, and even precipitation and stratification phenomena occur.

[0004] The binary or ternary copolymers disclosed in patents US6364918 and US6391071, such as diethanolamine derivatives of stearic acid acrylate-maleic anhydride copolymers, can be used as antiwear agents and low-temperature fluidity improvers for low-sulfur diesel, but they can only reduce the cold filter point of diesel, and the effect on the pour point depression of diesel is not obvious, and the latter is also an important indicator of my country's diesel quality standards. Patent US2009 / 0056203A1 discloses fatty acid-based low-sulfur diesel antiwear agents, but this carboxylic acid-based antiwear agent is easy to interact with the high base dispersant in diesel to generate calcium salts and magnesium salts, causing fuel filter screen blockage and metal corrosion. Patent CN1733874 discloses a method for preparing a mixture of amine salts of phosphate esters as a diesel additive, but phosphorus-containing antiwear additives are easy to affect the exhaust gas treatment device and have large side effects. Patent EP605857 discloses the use of natural oils such as rapeseed oil, castor oil, sunflower oil, etc. as diesel antiwear agents directly, but these products are added in large amounts and are easy to precipitate at low temperatures. Patent CN100999686 discloses a mixture of two components as a diesel antiwear agent, which can effectively improve the lubricity and low-temperature fluidity of diesel, but the preparation process of the components is relatively complicated. Patent CN104629868A discloses a low-sulfur diesel antiwear agent, the main component of which is fatty acid polyol ester. Patent CN101787318A discloses a mixture of glycerol monoesters and diesters and a dimer acid compound as a low-sulfur diesel antiwear agent. Summary of the invention

[0005] The purpose of the present invention is to propose an environmentally friendly low-sulfur diesel antiwear agent and its preparation method and application, and a low-sulfur diesel antiwear agent composition, which has excellent anti-wear performance, is not strongly acidic, has little effect on the use performance of diesel, such as corrosiveness, combustion performance, total acid value, oxidation stability, etc., can also improve the antioxidant performance of diesel, is compatible with engine oil, does not increase carbon deposits in the engine, and has broad application prospects.

[0006] The technical solution of the present invention is achieved in this way: The present invention provides an environmentally friendly low-sulfur diesel antiwear agent having a structure as shown in Formula I: Formula I.

[0007] The present invention further protects a method for preparing the above-mentioned environmentally friendly low-sulfur diesel antiwear agent, comprising the following steps: S1. Rapeseed oil, diethylenetriamine and a catalyst are mixed, xylene is added, and the mixture is heated and stirred under inert gas protection until the acid value of the mixture no longer changes. The catalyst is separated by centrifugation, the liquid is washed with sodium carbonate and then with hot water, and xylene and water are removed by vacuum distillation. The product is recrystallized with acetone to obtain an intermediate having the following structure: ; S2. The intermediate, ricinoleic acid and a catalyst are mixed, xylene is added, and the mixture is heated and stirred under inert gas protection until the acid value of the mixture no longer changes, the catalyst is separated by centrifugation, the liquid is washed with sodium carbonate and then with hot water, and xylene and water are removed by vacuum distillation. The product is recrystallized from a mixture of acetone and tetrahydrofuran to obtain an environmentally friendly low-sulfur diesel antiwear agent; The hot water is 60-80°C water.

[0008] As a further improvement of the present invention, the molar ratio of rapeseed oil and diethylenetriamine in step S1 is 1:1.1-1.2, the temperature of the heating and stirring reaction is 200-220°C, the amount of the catalyst added is 1-2wt% of the total mass of the reaction system in step S1, and the amount of xylene added is 5-10wt% of the total mass of the reaction system in step S1.

[0009] As a further improvement of the present invention, the molar ratio of the intermediate to ricinoleic acid in step S2 is 1:1-1.1, the temperature of the heating and stirring reaction is 100-120°C, the amount of the catalyst added is 1-2wt% of the total mass of the reaction system in step S2, and the amount of xylene added is 5-10wt% of the total mass of the reaction system in step S2.

[0010] As a further improvement of the present invention, the preparation method of the catalyst is as follows: T1. Preparation of silica nanospheres: adding alkyl orthosilicate to ethanol, adding water and ammonia, heating and stirring to react, centrifuging, washing, drying, and calcining to obtain silica nanospheres; T2. Preparation of modified silica nanospheres: adding silica nanospheres to water, adding tannic acid and a buffer salt catalyst, heating and stirring to react, centrifuging, washing, and drying to obtain modified silica nanospheres; T3. Preparation of calcium carbonate-coated silica nanospheres: adding modified silica nanospheres to water, adding calcium salt, stirring and mixing to obtain a suspension; adding sodium carbonate, sodium dodecyl sulfate and polyvinyl pyrrolidone to water, stirring and dissolving to obtain a mixed solution, adding the mixed solution to the suspension, stirring and reacting at room temperature, centrifuging, washing, and drying to obtain calcium carbonate-coated silica nanospheres; T4. Preparation of calcium oxide-coated silica nanospheres: Under the protection of an inert gas, the calcium carbonate-coated silica nanospheres were calcined to obtain calcium oxide-coated silica nanospheres; T5. Impregnation: dissolve the organic base in an organic solvent, add calcium oxide-coated silica nanospheres, impregnate overnight, centrifuge, wash, and dry to obtain a catalyst.

[0011] As a further improvement of the present invention, the alkyl orthosilicate in step T1 is methyl orthosilicate or ethyl orthosilicate, the mass ratio of the alkyl orthosilicate, ethanol, water, and ammonia water is 12-15:80-100:7-10:5-10, the temperature of the heating and stirring reaction is 40-50°C, the time is 7-10h, the temperature of the calcination is 450-550°C, and the time is 2-4h; the mass ratio of the silicon oxide nanospheres, tannic acid, and buffer salt catalyst in step T2 is 10-15:4-6:1-2, the buffer salt catalyst is a Tris-HCl solution with a pH of 8-9, the temperature of the heating and stirring reaction is 45-55°C, and the time is 2-4h.

[0012] As a further improvement of the present invention, the mass ratio of the modified silica nanospheres, calcium salt, sodium carbonate, sodium dodecyl sulfate and polyvinyl pyrrolidone in step T3 is 20-30:12-15:13-16:1-2:2-3, the calcium salt is selected from at least one of calcium chloride or calcium nitrate, and the reaction time of stirring at room temperature is 2-4h.

[0013] As a further improvement of the present invention, the calcination temperature in step T4 is 650-750° C. and the time is 1-2 h; the organic base in step T5 is selected from at least one of potassium tert-butoxide, sodium tert-butoxide, potassium ethoxide, and sodium methoxide, preferably a mixture of potassium tert-butoxide and potassium ethoxide, with a mass ratio of 10:3-5, and the mass ratio of the organic base to the calcium oxide-coated silicon oxide nanospheres is 1-2:10.

[0014] The invention prepares a catalyst, which takes nano silicon dioxide as the core, and the surface of which is modified by tannic acid so that the surface is rich in active groups such as carboxyl and hydroxyl groups. The calcium ions are fixed on the surface of the nano balls through chelation with calcium ions, thereby promoting in-situ reaction to generate a calcium carbonate shell layer, which is coated on the surface of the nano silicon dioxide. The calcium oxide-coated silicon oxide nano balls are obtained through calcination, and the calcium oxide-coated silicon oxide nano balls have the advantages of large specific surface area, rich catalytic active sites and the like. The catalyst formed by being able to be well compounded with an organic base has good particle dispersibility, large specific surface area and pore size distribution, and exhibits high activity. The nano structure provides rich active sites and accelerates mass transfer. After impregnation, the surface carries the same charge, which prevents aggregation and agglomeration of the active sites, so that the active sites on the surface of the material shell exhibit high activity, and the diffusion resistance of the reaction intermediates on the active sites is reduced, thereby improving the catalytic activity of the catalyst and reducing the occurrence of catalyst poisoning.

[0015] The present invention further protects the use of the above-mentioned environmentally friendly low-sulfur diesel antiwear agent in diesel.

[0016] The present invention further protects a low-sulfur diesel antiwear agent composition, which is prepared from the following raw materials: 8-10 parts of the above-mentioned environmentally friendly low-sulfur diesel antiwear agent and 5-7 parts of dihydroxy behenic acid.

[0017] The present invention has the following beneficial effects: The failure of diesel engine oil pumps is mainly caused by severe adhesive wear or abrasion, oxidation corrosion and fretting wear. Although low-sulfur diesel can reduce the direct contact between metal friction surfaces as a lubricant, the anti-wear film it forms is thin, and the oil film stability and mechanical strength are poor, which cannot effectively protect the friction surface. Therefore, by adding a small amount of polar anti-wear substances, a relatively strong organic adsorption film can be generated, thereby improving the ability of low-sulfur diesel to prevent adhesion.

[0018] The invention synthesizes an environmentally friendly low-sulfur diesel antiwear agent. The imidazoline is generated by dehydration reaction of rapeseed oil and diethylenetriamine, and further undergoes an amidation reaction with ricinoleic acid. The obtained product shows good anti-wear and friction-reducing effects on steel-steel friction pairs. The mechanism may be that N atoms contained in the prepared environmentally friendly low-sulfur diesel antiwear agent are adsorbed on the metal surface, and then chemical reactions occur during the friction process to generate a high-strength polymer film, thereby achieving a better anti-wear effect. At the same time, the ricinoleic acid part of the environmentally friendly low-sulfur diesel antiwear agent has a unique hydroxyl structure and unsaturated double bonds. This structural compound is more easily adsorbed on the friction interface to form an effective tough oil film, has strong oxidation resistance, good stability, and is degradable. It can effectively prevent problems such as metal hardening and adhesion of wear debris on the metal surface.

[0019] The environmentally friendly low-sulfur diesel antiwear agent prepared by the present invention has excellent antiwear performance, is not strongly acidic, has little effect on the use performance of diesel, such as corrosiveness, combustion performance, total acid value, oxidation stability, etc., can also improve the antioxidant performance of diesel, is compatible with engine oil, does not increase carbon deposits in the engine, and has broad application prospects.

[0020] The low-sulfur diesel antiwear agent composition of the present invention comprises an environmentally friendly low-sulfur diesel antiwear agent and dihydroxybehenic acid, which have a synergistic effect and can form a mesh polyester film through intermolecular dehydration. This film is firmly bonded to the metal friction pair, significantly improving the anti-wear performance, and is safe, environmentally friendly, biodegradable, and has broad application prospects. DETAILED DESCRIPTION

[0021] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0022] Preparation Example 1 Preparation of Catalyst Here’s how: T1. Preparation of silica nanospheres: 12 g of methyl orthosilicate was added to 80 g of ethanol, 7 g of water and 5 g of ammonia water, heated to 40°C, stirred for 7 h, centrifuged, washed, dried, and calcined at 450°C for 2 h to obtain silica nanospheres; T2. Preparation of modified silica nanospheres: 10 g of silica nanospheres were added to 200 mL of water, 4 g of tannic acid and 1 g of buffer salt catalyst were added, heated to 45°C, stirred for reaction for 2 h, centrifuged, washed, and dried to obtain modified silica nanospheres; The buffer salt catalyst is a Tris-HCl solution with a pH of 8; T3. Preparation of calcium carbonate-coated silica nanospheres: 20 g of modified silica nanospheres were added to 200 mL of water, and 12 g of calcium chloride was added, and the mixture was stirred for 15 min to obtain a suspension; 13 g of sodium carbonate, 1 g of sodium dodecyl sulfate and 2 g of polyvinyl pyrrolidone were added to 200 mL of water, and the mixture was stirred to dissolve to obtain a mixed solution, and the mixed solution was added dropwise to the suspension, and the mixture was stirred at room temperature for 2 h, centrifuged, washed and dried to obtain calcium carbonate-coated silica nanospheres; T4. Preparation of calcium oxide-coated silica nanospheres: Calcium carbonate-coated silica nanospheres were calcined at 650°C for 1 h under nitrogen protection to obtain calcium oxide-coated silica nanospheres; T5. Impregnation: 1 g of organic base was dissolved in 100 mL of dichloromethane, 10 g of calcium oxide-coated silica nanospheres were added, impregnated for 12 h, centrifuged, washed, and dried to obtain a catalyst; The organic base is a mixture of potassium tert-butoxide and potassium ethoxide, with a mass ratio of 10:3.

[0023] Preparation Example 2 Preparation of Catalyst Here’s how: T1. Preparation of silica nanospheres: 15 g of tetraethyl orthosilicate was added to 100 g of ethanol, 10 g of water and 10 g of ammonia water, heated to 50°C, stirred for 10 h, centrifuged, washed, dried, and calcined at 550°C for 4 h to obtain silica nanospheres; T2. Preparation of modified silica nanospheres: 15 g of silica nanospheres were added to 200 mL of water, 6 g of tannic acid and 2 g of buffer salt catalyst were added, heated to 55°C, stirred for 4 h, centrifuged, washed, and dried to obtain modified silica nanospheres; The buffer salt catalyst is a Tris-HCl solution with a pH of 9; T3. Preparation of calcium carbonate-coated silica nanospheres: 30 g of modified silica nanospheres were added to 200 mL of water, and 15 g of calcium nitrate was added, and the mixture was stirred for 15 min to obtain a suspension; 16 g of sodium carbonate, 2 g of sodium dodecyl sulfate and 3 g of polyvinyl pyrrolidone were added to 200 mL of water, and the mixture was stirred to dissolve to obtain a mixed solution, and the mixed solution was added dropwise to the suspension, and the mixture was stirred at room temperature for 4 h, centrifuged, washed and dried to obtain calcium carbonate-coated silica nanospheres; T4. Preparation of calcium oxide-coated silica nanospheres: Calcium carbonate-coated silica nanospheres were calcined at 750°C for 2 h under nitrogen protection to obtain calcium oxide-coated silica nanospheres; T5. Impregnation: 2 g of organic base was dissolved in 100 mL of dichloromethane, 10 g of calcium oxide-coated silica nanospheres were added, impregnated for 12 h, centrifuged, washed, and dried to obtain a catalyst; The organic base is a mixture of potassium tert-butoxide and potassium ethoxide, with a mass ratio of 10:5.

[0024] Preparation Example 3 Preparation of Catalyst Here’s how: T1. Preparation of silica nanospheres: 13 g of tetraethyl orthosilicate was added to 90 g of ethanol, 8 g of water and 7 g of ammonia water, heated to 45°C, stirred for 8 h, centrifuged, washed, dried, and calcined at 500°C for 3 h to obtain silica nanospheres; T2. Preparation of modified silica nanospheres: 12 g of silica nanospheres were added to 200 mL of water, 5 g of tannic acid and 1.5 g of buffer salt catalyst were added, heated to 50°C, stirred for reaction for 3 h, centrifuged, washed, and dried to obtain modified silica nanospheres; The buffer salt catalyst is a Tris-HCl solution with a pH of 8.5; T3. Preparation of calcium carbonate-coated silica nanospheres: 25 g of modified silica nanospheres were added to 200 mL of water, and 13 g of calcium chloride was added, and the mixture was stirred for 15 min to obtain a suspension; 14 g of sodium carbonate, 1.5 g of sodium dodecyl sulfate and 2.5 g of polyvinyl pyrrolidone were added to 200 mL of water, and the mixture was stirred to dissolve to obtain a mixed solution, and the mixed solution was added dropwise to the suspension, and the mixture was stirred at room temperature for 3 h, centrifuged, washed and dried to obtain calcium carbonate-coated silica nanospheres; T4. Preparation of calcium oxide-coated silica nanospheres: Under nitrogen protection, calcium carbonate-coated silica nanospheres were calcined at 700°C for 1.5 h to obtain calcium oxide-coated silica nanospheres; T5. Impregnation: 1.5 g of an organic base was dissolved in 100 mL of dichloromethane, 10 g of calcium oxide-coated silica nanospheres were added, and the mixture was impregnated for 12 h, centrifuged, washed, and dried to obtain a catalyst; The organic base is a mixture of potassium tert-butoxide and potassium ethoxide, with a mass ratio of 10:4.

[0025] Preparation Example 4 Compared with Preparation Example 3, the difference is that the organic base is single potassium tert-butoxide.

[0026] Preparation Example 5 Compared with Preparation Example 3, the difference is that the organic base is single potassium ethoxide.

[0027] Comparative Preparation Example 1 Compared with Preparation Example 3, the difference is that step T2 is not performed.

[0028] The details are as follows: T1. Preparation of silica nanospheres: 13 g of tetraethyl orthosilicate was added to 90 g of ethanol, 8 g of water and 7 g of ammonia water, heated to 45°C, stirred for 8 h, centrifuged, washed, dried, and calcined at 500°C for 3 h to obtain silica nanospheres; T2. Preparation of mixture 1: 25 g of silica nanospheres were added to 200 mL of water, 13 g of calcium chloride was added, and the mixture was stirred for 15 min to obtain a suspension; 14 g of sodium carbonate, 1.5 g of sodium dodecyl sulfate and 2.5 g of polyvinyl pyrrolidone were added to 200 mL of water, stirred to dissolve, and a mixed solution was obtained. The mixed solution was added dropwise to the suspension, stirred at room temperature for 3 h, centrifuged, washed, and dried to obtain a mixture 1; T3. Preparation of mixture 2: Under nitrogen protection, mixture 1 was calcined at 700 ° C for 1.5 h to obtain mixture 2; T4 impregnation: 1.5 g of an organic base was dissolved in 100 mL of dichloromethane, 10 g of mixture 2 was added, impregnated for 12 h, centrifuged, washed, and dried to obtain a catalyst; The organic base is a mixture of potassium tert-butoxide and potassium ethoxide, with a mass ratio of 10:4.

[0029] Comparative Preparation Example 2 Compared with Preparation Example 3, the difference is that steps T3 and T4 are not performed.

[0030] The details are as follows: T1. Preparation of silica nanospheres: 13 g of tetraethyl orthosilicate was added to 90 g of ethanol, 8 g of water and 7 g of ammonia water, heated to 45°C, stirred for 8 h, centrifuged, washed, dried, and calcined at 500°C for 3 h to obtain silica nanospheres; T2. Preparation of modified silica nanospheres: 12 g of silica nanospheres were added to 200 mL of water, 5 g of tannic acid and 1.5 g of buffer salt catalyst were added, heated to 50°C, stirred for reaction for 3 h, centrifuged, washed, and dried to obtain modified silica nanospheres; The buffer salt catalyst is a Tris-HCl solution with a pH of 8.5; T3. Impregnation: 1.5 g of an organic base was dissolved in 100 mL of dichloromethane, 10 g of modified silica nanospheres were added, and the mixture was impregnated for 12 h, centrifuged, washed, and dried to obtain a catalyst; The organic base is a mixture of potassium tert-butoxide and potassium ethoxide, with a mass ratio of 10:4 Comparative Preparation Example 3 Compared with Preparation Example 3, the difference is that step T5 is not performed.

[0031] The details are as follows: T1. Preparation of silica nanospheres: 13 g of tetraethyl orthosilicate was added to 90 g of ethanol, 8 g of water and 7 g of ammonia water, heated to 45°C, stirred for 8 h, centrifuged, washed, dried, and calcined at 500°C for 3 h to obtain silica nanospheres; T2. Preparation of modified silica nanospheres: 12 g of silica nanospheres were added to 200 mL of water, 5 g of tannic acid and 1.5 g of buffer salt catalyst were added, heated to 50°C, stirred for reaction for 3 h, centrifuged, washed, and dried to obtain modified silica nanospheres; The buffer salt catalyst is a Tris-HCl solution with a pH of 8.5; T3. Preparation of calcium carbonate-coated silica nanospheres: 25 g of modified silica nanospheres were added to 200 mL of water, and 13 g of calcium chloride was added, and the mixture was stirred for 15 min to obtain a suspension; 14 g of sodium carbonate, 1.5 g of sodium dodecyl sulfate and 2.5 g of polyvinyl pyrrolidone were added to 200 mL of water, and the mixture was stirred to dissolve to obtain a mixed solution, and the mixed solution was added dropwise to the suspension, and the mixture was stirred at room temperature for 3 h, centrifuged, washed and dried to obtain calcium carbonate-coated silica nanospheres; T4. Preparation of calcium oxide-coated silica nanospheres: Under nitrogen protection, calcium carbonate-coated silica nanospheres were calcined at 700° C. for 1.5 h to obtain calcium oxide-coated silica nanospheres, which were catalysts.

[0032] Test Example 1 The specific surface area and pore volume of the catalysts prepared in Preparation Examples 1-5 and Comparative Preparation Examples 1-3 were measured using an ASAP2460 fully automatic specific surface and porosity analyzer. The results are shown in Table 1.

[0033] Table 1 ; It can be seen from the above table that the catalysts prepared in Preparation Examples 1-5 of the present invention have larger specific surface areas and total pore volumes, among which the catalyst prepared in Preparation Example 3 has the largest specific surface area and total pore volume. Example 1

[0034] This embodiment provides a method for preparing an environmentally friendly low-sulfur diesel antiwear agent.

[0035] The synthetic route is as follows: .

[0036] The following steps are involved: S1. 1 mol of rapeseed oil, 1.1 mol of diethylenetriamine and the catalyst prepared in Preparation Example 1 were mixed, and xylene was added, wherein the amount of the catalyst added was 1 wt% of the total mass of the reaction system in step S1, and the amount of the xylene added was 5 wt% of the total mass of the reaction system in step S1. Under nitrogen protection, the mixture was heated to 200°C and stirred for reaction until the acid value of the mixture no longer changed. The catalyst was separated by centrifugation, the liquid was washed with sodium carbonate, and then with water at 60-80°C, and the xylene and water were removed by vacuum distillation. The product was recrystallized from acetone to obtain an intermediate; ESI-MS calculated value: C 12 H 23 N4O3S2(M+H) + 335.11, found value: 335.1, yield: 91%.

[0037] NMR results: 1 H NMR (300MHz, CDCl3) δ8.0 (br, 1H), 4.46 (t, 1H), 3.49 (t, 4H), 3.32 (s, 4H), 2.85-2.93 (m, 6H), 2.45-2.58 (m, 2H), 2.0 (br, 4H).

[0038] S2. Mix 1 mol of the intermediate, 1 mol of ricinoleic acid and the catalyst prepared in Preparation Example 1, add xylene, the amount of the catalyst added is 1wt% of the total mass of the reaction system in step S2, and the amount of xylene added is 5wt% of the total mass of the reaction system in step S2. Heat to 100°C under nitrogen protection, stir and react until the acid value of the mixture no longer changes, centrifuge to separate the catalyst, wash the liquid with sodium carbonate, then wash with water at 60-80°C, remove xylene and water by vacuum distillation, and recrystallize the product with a mixed solution of acetone and tetrahydrofuran (volume ratio 1:1) to obtain an environmentally friendly low-sulfur diesel antiwear agent. ESI-MS calculated value: C 30 H 53 N4O4S2(M+H) + 597.34, found value: 597.3, yield: 93%.

[0039] NMR results: 1H NMR (300MHz, CDCl3) δ8.2 (br, 2H), 5.45 (d, 2H), 4.42 (t, 1H), 3.32-3.34 (m, 4H), 3.25 (m, 1H), 2.8-2.9 (m, 4H), 2.62 ( t, 2H), 2.5 (s, 2H), 2.4-2.5 (m, 2H), 2.19-2.22 (m, 3H), 1.9-2.0 (m, 4H), 1.57 (m, 2H), 1.3-1.5 (m, 20H), 0.96 (t, 3H). Example 2

[0040] This embodiment provides a method for preparing an environmentally friendly low-sulfur diesel antiwear agent, comprising the following steps: S1. 1 mol of rapeseed oil, 1.2 mol of diethylenetriamine and the catalyst prepared in Preparation Example 2 were mixed, and xylene was added, wherein the amount of the catalyst added was 2 wt % of the total mass of the reaction system in step 1, and the amount of the xylene added was 10 wt % of the total mass of the reaction system in step S1. Under nitrogen protection, the mixture was heated to 220° C. and stirred for reaction until the acid value of the mixture no longer changed. The catalyst was separated by centrifugation, and the liquid was washed with sodium carbonate and then with water at 60-80° C. The xylene and water were removed by distillation under reduced pressure, and the product was recrystallized from acetone to obtain an intermediate with a yield of 92%; S2. 1 mol of the intermediate, 1.1 mol of ricinoleic acid and the catalyst prepared in Preparation Example 2 are mixed, and xylene is added, wherein the amount of the catalyst added is 2 wt% of the total mass of the reaction system in step S2, and the amount of the xylene added is 10 wt% of the total mass of the reaction system in step S2. Under nitrogen protection, the mixture is heated to 120°C and stirred for reaction. The mixture is reacted until the acid value of the mixture no longer changes, and the catalyst is separated by centrifugation. The liquid is washed with sodium carbonate and then with water at 60-80°C. The xylene and water are removed by vacuum distillation. The product is recrystallized from a mixture of acetone and tetrahydrofuran (volume ratio 1:1) to obtain an environmentally friendly low-sulfur diesel antiwear agent with a yield of 94%. Example 3

[0041] This embodiment provides a method for preparing an environmentally friendly low-sulfur diesel antiwear agent, comprising the following steps: S1. 1 mol of rapeseed oil, 1.15 mol of diethylenetriamine and the catalyst prepared in Preparation Example 3 were mixed, and xylene was added, wherein the amount of the catalyst added was 1.5 wt% of the total mass of the reaction system in step S1, and the amount of the xylene added was 7 wt% of the total mass of the reaction system in step S1. Under nitrogen protection, the mixture was heated to 210° C. and stirred for reaction until the acid value of the mixture no longer changed. The catalyst was separated by centrifugation, and the liquid was washed with sodium carbonate and then with water at 60-80° C. The xylene and water were removed by distillation under reduced pressure. The product was recrystallized from acetone to obtain an intermediate with a yield of 94%; S2. 1 mol of the intermediate, 1.05 mol of ricinoleic acid and the catalyst prepared in Preparation Example 3 are mixed, and xylene is added, wherein the amount of the catalyst added is 1.5 wt% of the total mass of the reaction system in step S2, and the amount of the xylene added is 7 wt% of the total mass of the reaction system in step S2. Under nitrogen protection, the mixture is heated to 110°C and stirred for reaction. The mixture is reacted until the acid value of the mixture no longer changes, and the catalyst is separated by centrifugation. The liquid is washed with sodium carbonate and then with water at 60-80°C. The xylene and water are removed by distillation under reduced pressure. The product is recrystallized from a mixture of acetone and tetrahydrofuran (volume ratio 1:1) to obtain an environmentally friendly low-sulfur diesel antiwear agent with a yield of 95%. Example 4

[0042] Compared with Example 3, the difference is that the catalyst is prepared by Preparation Example 4. Example 5

[0043] Compared with Example 3, the difference is that the catalyst is prepared by Preparation Example 5.

[0044] Comparative Example 1 Compared with Example 3, the difference is that the catalyst is prepared by Comparative Preparation Example 1.

[0045] Comparative Example 2 Compared with Example 3, the difference is that the catalyst is prepared by Comparative Preparation Example 2.

[0046] Comparative Example 3 Compared with Example 3, the difference is that the catalyst is prepared by Comparative Preparation Example 3.

[0047] Test Example 2 The reactions in Examples 1-5 of the present invention and Comparative Examples 1-3 were evaluated, and the results are shown in Table 2.

[0048] Table 2 ; It can be seen from the above table that the yields of the environmentally friendly low-sulfur diesel anti-wear agent in Examples 1-5 of the present invention are relatively high, among which the yield of the environmentally friendly low-sulfur diesel anti-wear agent in Example 3 is the highest. Example 6

[0049] A low-sulfur diesel antiwear agent composition is prepared by mixing the following raw materials in parts by weight: 8 parts of the environmentally friendly low-sulfur diesel antiwear agent prepared in Example 3 and 5 parts of dihydroxybehenic acid. Example 7

[0050] A low-sulfur diesel antiwear agent composition is prepared by mixing the following raw materials in parts by weight: 10 parts of the environmentally friendly low-sulfur diesel antiwear agent prepared in Example 3 and 7 parts of dihydroxybehenic acid. Example 8

[0051] A low-sulfur diesel antiwear agent composition is prepared by mixing the following raw materials in parts by weight: 9 parts of the environmentally friendly low-sulfur diesel antiwear agent prepared in Example 3 and 6 parts of dihydroxybehenic acid.

[0052] Test Example 3 The environmentally friendly low-sulfur diesel antiwear agent prepared in Example 3 and the low-sulfur diesel antiwear agent composition prepared in Examples 6-8 were tested for acid value. The results are shown in Table 3.

[0053] Table 3 ; It can be seen from the above table that the environmentally friendly low-sulfur diesel antiwear agent prepared in Example 3 of the present invention and the low-sulfur diesel antiwear agent composition prepared in Examples 6-8 have lower acid values.

[0054] Test Example 4: Evaluation of anti-wear effect The environmentally friendly low-sulfur diesel antiwear agent prepared in Example 3, the low-sulfur diesel antiwear agent composition prepared in Examples 6-8, rapeseed oil, and ricinoleic acid were added to low-sulfur diesel in an amount of 100 mg / kg to evaluate the antiwear effect. The operating conditions of the four-ball machine in the laboratory were: (1) load 15 kg, (2) speed 1500 r / min, (3) time 30 min, and (4) temperature: room temperature. The results are shown in Table 4.

[0055] Table 4 ; It can be seen from the above table that the environmentally friendly low-sulfur diesel antiwear agent prepared in Example 3 of the present invention and the low-sulfur diesel antiwear agent composition prepared in Examples 6-8 have good antiwear effects.

[0056] Test Example 5 The environmentally friendly low-sulfur diesel antiwear agent prepared in Example 3, the low-sulfur diesel antiwear agent composition prepared in Examples 6-8, rapeseed oil and ricinoleic acid were added to low-sulfur diesel in an amount of 100 mg / kg. The pour point of the low-sulfur diesel was 20°C and the cold filter point was -11°C. The performance was tested.

[0057] Refer to GB / T5096-2017 "Petroleum Products Copper Strip Corrosion Test Method" to test whether the anti-wear agent causes corrosion to the copper strip.

[0058] Refer to SH / T0175-2004 "Determination of oxidation stability of distillate fuel oil (accelerated method)" to test the effect of anti-wear agent on the oxidation stability of diesel.

[0059] The results are shown in Table 5.

[0060] Table 5 ; It can be seen from the above table that the environmentally friendly low-sulfur diesel antiwear agent prepared in Examples 1-3 of the present invention and the low-sulfur diesel antiwear agent composition prepared in Examples 6-8 have little effect on the pour point and cold filter point of diesel, which change within 0.5°C, and will not cause corrosion to copper sheets, and have little effect on the oxidation stability of diesel.

[0061] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. An environmentally friendly low-sulfur diesel antiwear agent, characterized in that: Having the structure shown in Formula I: Formula I.

2. A method for preparing an environmentally friendly low-sulfur diesel antiwear agent as claimed in claim 1, characterized in that: The following steps are involved: S1. Rapeseed oil, diethylenetriamine and a catalyst are mixed, xylene is added, and the mixture is heated and stirred under inert gas protection until the acid value of the mixture no longer changes. The catalyst is separated by centrifugation, the liquid is washed with sodium carbonate and then with hot water, and xylene and water are removed by vacuum distillation. The product is recrystallized with acetone to obtain an intermediate having the following structure: ; S2. The intermediate, ricinoleic acid and a catalyst are mixed, xylene is added, and the mixture is heated and stirred under inert gas protection until the acid value of the mixture no longer changes, the catalyst is separated by centrifugation, the liquid is washed with sodium carbonate and then with hot water, and xylene and water are removed by vacuum distillation. The product is recrystallized from a mixture of acetone and tetrahydrofuran to obtain an environmentally friendly low-sulfur diesel antiwear agent; The hot water is 60-80°C water.

3. The preparation method according to claim 2, characterized in that: The molar ratio of rapeseed oil and diethylenetriamine in step S1 is 1:1.1-1.2, the temperature of the heating and stirring reaction is 200-220°C, the amount of the catalyst added is 1-2wt% of the total mass of the reaction system in step S1, and the amount of xylene added is 5-10wt% of the total mass of the reaction system in step S1.

4. The preparation method according to claim 2, characterized in that: The molar ratio of the intermediate to ricinoleic acid in step S2 is 1:1-1.1, the temperature of the heating and stirring reaction is 100-120°C, the amount of the catalyst added is 1-2wt% of the total mass of the reaction system in step S2, and the amount of xylene added is 5-10wt% of the total mass of the reaction system in step S2.

5. The preparation method according to claim 2, characterized in that: The preparation method of the catalyst is as follows: T1. Preparation of silica nanospheres: adding alkyl orthosilicate to ethanol, adding water and ammonia, heating and stirring to react, centrifuging, washing, drying, and calcining to obtain silica nanospheres; T2. Preparation of modified silica nanospheres: adding silica nanospheres to water, adding tannic acid and a buffer salt catalyst, heating and stirring to react, centrifuging, washing, and drying to obtain modified silica nanospheres; T3. Preparation of calcium carbonate-coated silica nanospheres: adding modified silica nanospheres to water, adding calcium salt, stirring and mixing to obtain a suspension; adding sodium carbonate, sodium dodecyl sulfate and polyvinyl pyrrolidone to water, stirring and dissolving to obtain a mixed solution, adding the mixed solution to the suspension, stirring and reacting at room temperature, centrifuging, washing, and drying to obtain calcium carbonate-coated silica nanospheres; T4. Preparation of calcium oxide-coated silica nanospheres: Under the protection of an inert gas, the calcium carbonate-coated silica nanospheres were calcined to obtain calcium oxide-coated silica nanospheres; T5. Impregnation: dissolve the organic base in an organic solvent, add calcium oxide-coated silica nanospheres, impregnate overnight, centrifuge, wash, and dry to obtain a catalyst.

6. The preparation method according to claim 5, characterized in that: The alkyl orthosilicate in step T1 is methyl orthosilicate or ethyl orthosilicate, the mass ratio of the alkyl orthosilicate, ethanol, water and ammonia water is 12-15:80-100:7-10:5-10, the temperature of the heating and stirring reaction is 40-50°C, the time is 7-10h, the temperature of the calcination is 450-550°C, and the time is 2-4h; the mass ratio of the silicon oxide nanospheres, tannic acid and buffer salt catalyst in step T2 is 10-15:4-6:1-2, the buffer salt catalyst is a Tris-HCl solution with a pH of 8-9, the temperature of the heating and stirring reaction is 45-55°C, and the time is 2-4h.

7. The preparation method according to claim 5, characterized in that: The mass ratio of the modified silica nanospheres, calcium salt, sodium carbonate, sodium dodecyl sulfate and polyvinyl pyrrolidone in step T3 is 20-30:12-15:13-16:1-2:2-3, the calcium salt is selected from at least one of calcium chloride or calcium nitrate, and the reaction time under room temperature stirring is 2-4 hours.

8. The preparation method according to claim 5, characterized in that: The calcination temperature in step T4 is 650-750° C. and the time is 1-2 hours; the organic base in step T5 is a mixture of potassium tert-butoxide and potassium ethoxide in a mass ratio of 10:3-5, and the mass ratio of the organic base to the calcium oxide-coated silicon oxide nanospheres is 1-2:

10.

9. Use of the environmentally friendly low-sulfur diesel antiwear agent as claimed in claim 1 in diesel.

10. A low-sulfur diesel antiwear agent composition, characterized in that: The invention is prepared from the following raw materials: 8-10 parts of the environmentally friendly low-sulfur diesel antiwear agent according to claim 1 and 5-7 parts of dihydroxybehenic acid.

Citation Information

Patent Citations

  • Improver for lubricating performance of low-sulfur diesel oil and preparation process thereof

    CN101787318A

  • Preparation method of low-sulfur diesel oil antiwear agent

    CN104629868A

  • Low sulfur mineral Diesel fuel oil

    EP0605857A1

  • Branched carboxylic acids as fuel lubricity additives

    US20090056203A1

  • Hydroxyl-containing copolymers, and their use for the preparation of fuel oils having improved lubricity

    US6364918B1

Cited By

  • Diesel oil anti-wear agent and preparation process thereof

    CN121538004A

  • Acid ester compound type diesel oil anti-wear agent and preparation method thereof

    CN121736827A